Bilateral Inguinal Hernia Containing both Ovaries in an Infant (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
Inguinal hernia with uncommon contents in the hernia sac has been reported in the literature. Preoperative ultrasound can be helpful to diagnose the presence an uncommon content in the hernia sac. Here we report a rare case of female infant having bilateral inguinal hernia with sac containing ovary and fallopian tube with left sided torsion ovary.DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21075